Performance Evaluation Zeta Converter Using PI Controller for Energy Management in DC Nanogrid Isolated System - Murdianto, Farid Dwi; Sudiharto, Indhana; Wulandari, Eni (Politeknik Negeri Ujung Pandang, 2021)
Renewable energy is needed as an alternative energy source. One of the implementations of renewable energy is the Solar Power Plant (PLTS). PLTS is a component that uses solar cells to convert solar energy into electrical energy. Unfortunately, the output power of this solar cell depends on the intensity of the light which causes the output power to enter the load to be unstable. Sometimes the PV power decrease because of the shading effect. From this problem a converter is needed to keep the system output voltage. The converter used in this research is the zeta converter. This Zeta converter can operate like a buck boost converter. The output of the system used is not stable. So that to stabilize it requires good control. In this paper using PI controller to control this system in order to keep the output system stable. 3. The error generated using the PI Control on the system is only 0.34%.